Labour shares and the role of capital and labour market imperfections - Lena Suchanek (Bank of Canada, 2009)
In continental Europe, labour shares in national income have exhibited considerable variation since 1970. Empirical and theoretical research suggests that the evolution of labour markets and labour market imperfections can, in part, explain this phenomenon. The author analyzes the role of capital market imperfections in the determination of the distribution of national income, comparing European and Anglo-Saxon countries. She uses a simple general-equilibrium model to trace the effects of credit and labour market imperfections on factor shares. Simulations indicate that improvements in capital markets can explain lower labour shares. An increase in the degree of employee power results in higher labour shares. Regression results confirm the author's findings. Improvements in credit markets and decreasing employee bargaining power have contributed to shrinking labour shares, especially in Europe. Openness is a negative determinant of labour shares.
Keywords: C78; E25; J64; 330; Economic models; Labour markets; Financial institutions; Volkseinkommen; Lohnquote; Arbeitsmarktungleichgewicht; Finanzmarkt; Vergleich; Europa; Großbritannien; Nordamerika